Knowledge, attitude and practice of Malaysian public university students on risk factors for cardiovascular diseases - Ibrahim, Mardhiah Mahada; A. Rahman, Nor Azlina; A.Rahman, Nor Iza; Haque, Mainul (Journal of Applied Pharmaceutical Science, 2016)
Cardiovascular diseases (CVD) account for 30% of all deaths in Malaysia. Major risk factors for CVD include age, gender, heredity, hypertension, cigarette smoking, hypercholesterolemia, diabetes, obesity and physical inactivity. The current study was conducted to understand the knowledge, attitude and practice (KAP) of University students regarding cardiovascular diseases. This is a cross-sectional study using a stratified random sampling method. Students of all faculties of International Islamic University Malaysia (IIUM) in Kuantan Campus were included. The respondents were randomly selected from each faculty. The sample size was 163. KAP questionnaire was developed and distributed to the respondents involved. The data collected was analyzed using SPSS version 17.0. The mean and standard deviation of the knowledge, attitude and practice scores were 42.98±2.46, 57.12±5.73 and 26.7±3.507, respectively. Significant difference on knowledge scores were found between different faculties (p<0.001), also on attitude and practice scores in comparison between different genders (p = 0.005 and 0.017, respectively). This study also shows a significant positive correlation between attitude and practice scores (r=+0.354, p<0.001). IIUM students should engage in exercise more and develop a healthier lifestyle.